Effect of Soil Depth on Growth and Water Consumption of Young Vitis vinifera L. cv. Pinot noir - Myburgh, P.A.; Van Zyl, J.L.; Conradie, W.J (South African Journal of Enology and Viticulture, 2017)
There is uncertainty about the optimum soil preparation depth for vineyards and to what extent irrigation can compensate for insufficient soil depth. Pinot noir was planted under non-irrigated conditions to soil preparation depths of 200 mm, 400 mm, 600 mm, 800 mm, 1 000 mm and 1 200 mm. Field lysimeters of 400 mm, 800 mm and 1 200 mm depths were constructed to study the effect of irrigation and to facilitate accurate measurement of water consumption. Vegetative growth and physiological activities responded positively to increasing soil depth under dryland conditions as well as under irrigation. Irrigation improved vegetative growth compared to non-irrigated treatments of corresponding depths. Under dryland conditions optimum vegetative growth and physiological response were achieved during the third year with 800 mm and 1 000 mm soil depths. Loosening the soil to 1 200 mm induced excessive growth on a lengthened Perold trellising system. Irrigation stimulated vigour and consequently sufficient vegetative growth was achieved at the end of the second season for 800 mm and 1 200 mm deep soil. This situation was only attained at the end of the third season for 400 mm deep irrigated soil. At this stage irrigation stimulated excessive vigour for 800 mm and 1 200 mm deep soils. Water consumption of irrigated vines increased during the first three years after planting. During the third year, water consumption of the 800 mm irrigated treatment was comparable to the 500 mm generally regarded as the norm for full-bearing vines in the coastal region of the Western Cape. Increased vegetative growth induced by increased soil depth reflected clearly in evapotranspiration. Three-year-old vines, which grew too vigorously on 1 200 mm deep soil, consumed 614 mm of water.  On the other hand, where 400 mm soil depth limited growth, water consumption amounted to only 387 mm. During the first and second seasons irrigation should be reduced to 44,6% and 65,5% respectively of the irrigation generally required by bearing grapevines.